2020
DOI: 10.1088/1742-5468/ab99c0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of single-file pedestrian movement with height constraints

et al.

Abstract: In the case of a fire, the presence of smoke sometimes makes people bend over and thus prevents them from walking upright. This feature of pedestrian movement in this situation is different from normal walking and affects the dynamics of an evacuation. However, the effect of such kind of motion on pedestrian traffic has not been systematically studied. Therefore, this paper studies the characteristics of pedestrian motion when different heights are available through a series of single-file experiments. In tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…Their average age is 23.6 ranging from 19 to 28, while their average height is 166 cm ranging from 155 to 183 cm. Different from the movement on level plane [15][16][17], the movement on the stairs is a little complex and can be divided into three stages, namely, descending, level movement and ascending. Two types of obstacle were considered.…”
Section: (C)mentioning
confidence: 99%
“…Their average age is 23.6 ranging from 19 to 28, while their average height is 166 cm ranging from 155 to 183 cm. Different from the movement on level plane [15][16][17], the movement on the stairs is a little complex and can be divided into three stages, namely, descending, level movement and ascending. Two types of obstacle were considered.…”
Section: (C)mentioning
confidence: 99%
“…In fact, except for crawling, there is another posture suitable for evacuation. It has been reported that pedestrian moving posture can evolve from normal walking, stoop walking, and crawling in sequence due to the gradual decline of the smoke layer (Yang et al 2012, Zheng et al 2017, Cao et al 2018a, Ma et al 2020a, Ma et al 2020b. Stoop walking could be a promising way to safely escape a fire, but as yet, only a few studies have been found to focus on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…The result demonstrated that the mean speed of upright walking, stoop walking and knee and hand crawling were 1.93, 1.84 and 0.84 m s −1 , respectively. More recently, Ma et al (2020b) extracted the density-speed fundamental diagrams from a single-file experiment where pedestrians changed their posture from keeping upright to stoop walking in an oval-like corridor under five different height constraints. They found an interesting result that the free speed of pedestrians at the constraint height of 1.4 m reached as high as 1.42 m s −1 , which was greater than that obtained at the other four heights (0.95 m s −1 at 1 m, 1.30 m s −1 at 1.2 m, 1.19 m s −1 at 1.6 m, and 1.35 m s −1 at 2.0 m).…”
Section: Introductionmentioning
confidence: 99%
“…Stop-and-go behavior is more frequent, and pedestrians stop longer time with music. In Ma et al (2020), pedestrians bend to walk due to height constraints in the experiments. The maximum velocity occurs at an intermediate height constraint, due to the posture and gravity center of pedestrians.…”
Section: Introductionmentioning
confidence: 99%